Therapeutic options for management of Hori's nevus: A systematic review. Issue 1 (3rd December 2019) - Kaur, Harpinder; Sarma, Phulen; Kaur, Sukhmandeep; Kaur, Hardeep; Prajapat, Manisha; Mahendiratta, Saniya; Kumar, Subodh; Thota, Prasad; Parsad, Davinder; Medhi, Bikash
Abstract: Hori's nevus is a pigmentation disorder reported mainly in middle‐aged Asian women. There is no systematic review addressing its pharmacotherapy. The population for our systematic review was patients with a clinical/histological diagnosis of Hori's nevus (both sex, any age group). We screened five literature databases using relevant keywords. All RCTs, observational studies and case series mentioning at least one intervention and outcome of that intervention were included. Nineteen studies were included in the final systematic review from total 680 identified nonduplicate records. Different forms of laser (alexandrite laser [QSAL and PSAL], Nd:YAG laser [QSNYL high fluence, low fluence, 532 followed by 1064 nm], Er: YAG and Nd:YAG combination, ruby laser [QSRL], CO2 laser followed by QSRL) and dermabrasion were found to be useful in treatment of Hori' nevus. Among alexandrite lasers, PSAL is more efficacious and safe than QSAL. In case of high fluence QSNYL, hyperpigmentation rate is quite high while low fluence QSNYL requires more number of treatment sessions. The combined 1064 nm + 532 nm protocol is better in terms of efficacy and safety. Er:YAG + Nd:YAG combination have similar efficacy and added advantage of synergistic action and no adverse event.